1989
DOI: 10.1111/j.1432-1033.1989.tb14618.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of trypsin from the poikilotherm Gadus morhua

Abstract: A serine protease shown to be trypsin was purified from the pyloric caeca of Atlantic cod (Gadus morhua), and resolved into three differently charged species by chromatofocusing (PI 6.6,6.2 and 5.5). All three trypsins had similar molecular mass of 24.2 kDa. N-terminal amino acid sequence analysis of cod trypsin showed considerable similarity with other known trypsins, particularily with dogfish and some mammalian trypsins. The apparent K, values determined at 25 "C for the predominant form of Atlantic cod try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
142
3
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(164 citation statements)
references
References 48 publications
18
142
3
1
Order By: Relevance
“…Multiple numbers of these amino acids are frequently found within proteins that can explain the deactivation of a wide spectrum of viruses by ColdZyme. Trypsin from Atlantic cod (Gadus morhua) has been shown to have higher catalytic efficiency than comparable enzymes [11][12][13][14][15]. Furthermore, native proteins, such as those found on the surface of viruses, appear to be more readily hydrolyzed by cod trypsin [15].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple numbers of these amino acids are frequently found within proteins that can explain the deactivation of a wide spectrum of viruses by ColdZyme. Trypsin from Atlantic cod (Gadus morhua) has been shown to have higher catalytic efficiency than comparable enzymes [11][12][13][14][15]. Furthermore, native proteins, such as those found on the surface of viruses, appear to be more readily hydrolyzed by cod trypsin [15].…”
Section: Discussionmentioning
confidence: 99%
“…Trypsins from most marine organisms studied are anionic and in most cases more than one form is found (Asgeirsson et al, 1989). For trypsin from the North Atlantic salmon, for example, there are three forms with pl values of 5.3, 4.8 and 4.7, respectively (Arnesen, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the fish trypsins have a temperature optimum similar to the mammalian enzymes, but several trypsins from marine sources are less stable at higher temperatures than their mammalian equivalents (Hjelmeland & Raa, 1982;Asgeirsson et al, The lower working temperature found for fish trypsins and the other properties unique for these fish enzymes as described above, are most likely related to the three-dimensional structure, and interests in gene modification of fish trypsins have recently been expressed (Nordisk Industrifond Protein Engineering Programme, Inaugural Symposium, September, 1989). We therefore initiated a structure study of trypsins from different fish species (Smalls, 1990;Smalhs, Hordvik, Hansen, Hough, Jynge, 1990), and the results from a 1.82 A X-ray crystallographic structure study of trypsin from the North Atlantic salmon (Salmo salar) as found in crystal form I (Smalls et al, 1990) are presented here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25) These trypsins display substantially higher catalytic efficiency than their mammalian counterparts. [25][26][27][28][29][30][31][32][33] We previously reported the chum salmon trypsin-catalyzed synthesis of peptides using inverse substrates. 23,24) We had obtained commercially available Atlantic cod trypsin at almost the same time.…”
mentioning
confidence: 99%